(untitled) (Research, Society and Development, 2024)
Herpes Zoster is a disease marked by the Varicella-Zoster Virus (VZV) reactivation. The ophthalmic branch of the trigeminal nerve can be affected by the pathogen, causing Herpes Zoster Ophthalmicus (HZO). In this context, the virus reactivation in the ophthalmic branch of the trigeminal nerve was frequently described in the literature as possibly associated with vaccination against SARS-CoV-2. Such occurrences were scarce, but statistically significant. The studies also pointed out a unique pattern in the proportion of people affected by HZ according to the nature of the vaccine, so that those using mRNA as an antigen were the most frequent. Thus, this study aimed to report the case of a 23-year-old Brazilian woman, immunocompetent, who developed HZO about a month and a half after taking the second dose of CoronaVac®, an inactivated virus vaccine, and complained of pain in the form of stabbing and burning in the supraorbital and orbital regions of the left hemiface, culminating in the formation of painful and reddish vesicular lesions. It is concluded that there is evidence linking vaccination and the reported reactivation. Therefore, it is important to disseminate these data among health professionals in order to ensure the safety of vaccination of individuals who are part of the risk group, without discouraging their immunization.